Contemporary International Law and Technological Progress: Theoretical Aspects - M. V. Shugurov (Московский журнал международного права)
The article is devoted to various aspects of correlation modern international law and technological progress. Much attention is paid to key tendencies of development of the international legal order in global context of high technologies. The author develops offers on perfection of balance of MDGs and states interests in science and technological areas. The article evaluates the international scientific and technological cooperation as a direction in contemporary world development. The analysis of role of international law in the technological progress is made based on various international legal acts and international legal doctrine. Author emphasizes the need for understanding of modern international law as valuable tool for international cooperation in the sphere of transfer of technology. Currently the international law is understood as a legal dimension of scientific and technological space.